2017
DOI: 10.1080/13854046.2016.1277557
|View full text |Cite
|
Sign up to set email alerts
|

The statistical crisis in science: how is it relevant to clinical neuropsychology?

Abstract: There is currently a statistical (and replication) crisis in science. Social psychology has been at the heart of this crisis, but the lessons learned are relevant for other fields. We discuss three examples of replication challenges and some proposed solutions, and then consider the applicability of these ideas to clinical neuropsychology. In addition to procedural developments such as preregistration and open data and criticism, we recommend that data be collected and analyzed with more recognition that each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…In light of this empirical consideration, our own findings of poor reliability might be considered as reflecting spurious results that can arise when VOI-based structural brain behavior correlations are performed in healthy adult cohorts with possibly noisy measurements. Thus, together and in line with the recent replication crisis Gelman and Geurts 2017), the present study emphasizes that low effect size in noisy brain-behavior correlation should be taken with caution rather than indicative of a robust feature of brain-behavior relationship.…”
Section: Significant Structural Brain Behavior Correlation and The Nementioning
confidence: 51%
“…In light of this empirical consideration, our own findings of poor reliability might be considered as reflecting spurious results that can arise when VOI-based structural brain behavior correlations are performed in healthy adult cohorts with possibly noisy measurements. Thus, together and in line with the recent replication crisis Gelman and Geurts 2017), the present study emphasizes that low effect size in noisy brain-behavior correlation should be taken with caution rather than indicative of a robust feature of brain-behavior relationship.…”
Section: Significant Structural Brain Behavior Correlation and The Nementioning
confidence: 51%
“…Our study therefore speaks directly to the “replication crisis” that is currently being highlighted in psychology and neuroscience ( Forstmeier et al, 2017 , Gelman and Geurts, 2017 , Ioannidis, 2005 , Loken and Gelman, 2017 , Munafò et al, 2017 , Pashler and Wagenmakers, 2012 ). In the field of psychology, for example, a large-scale collaborative initiative reported that it could only successfully replicate less than 40% of original effects from a representative set of one hundred randomly selected studies ( Open Science Collaboration, 2015 ).…”
Section: Introductionmentioning
confidence: 70%
“…Another problem is related to statistics, where Gelman and Geurts (2017) explained three examples of findings in social psychology indicating "a replication crisis". One of them is related to a statistical error in removing data, for instance, few par-ticipants are removed from the analysis with a certain purpose, either to confirm a hypothesis or to remove outliers in order to have normally distributed data.…”
Section: Challenges Of Replication In Psychologymentioning
confidence: 99%
“…Based on the explanation of replication study issues in Indonesia and the recommendations to resolve the issues as suggested by Asendorpt et al (2013) and Gelman and Geurts (2017), it can be concluded that the essential thing to support the increase of replication studies and to strengthen the findings of replication studies in Indonesia is by increasing the understanding of research methods and basic statistical methods. Psychology lecturers in Indonesia should be open to information and new understanding of replication studies as an effort to strengthen the results of study and theoretical concepts.…”
Section: Scientific Communicationmentioning
confidence: 99%